Evaluate 7 + (-3x2) for x = 0.
-2
0
4
7

Question

Asked 10/5/2012 10:59:29 AM

Updated 8/6/2014 6:57:07 PM

6 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [8/6/2014 6:53:54 PM]

s

leo4797|Points 10|

leo4797|Points 10|

latefisher|Points 3058|

Dakd123|Points 10|

stan_r|Points 1382|

Question

Asked 10/5/2012 10:59:29 AM

Updated 8/6/2014 6:57:07 PM

6 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [8/6/2014 6:53:54 PM]

Rating

8

when x = 0,

7 + (-3x^2) = 7 - 3x^2 = 7 - 3(0^2) = 7 - 0 = 7

7 + (-3x^2) = 7 - 3x^2 = 7 - 3(0^2) = 7 - 0 = 7

Added 8/6/2014 6:53:51 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/6/2014 6:57:16 PM]

8

21 - 18 ÷ 3 · 2 = 21 - 6*2 = 21 - 12 = 9

Added 8/6/2014 6:54:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/6/2014 6:57:59 PM]

8

7(x + 3) = 7x + 21

Added 8/6/2014 6:55:02 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/6/2014 6:58:42 PM]

8

9 - {x - (7 + x)} = 9 - (x - 7 - x) = 9 - (-7) = 9 + 7 = 16

Added 8/6/2014 6:55:57 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/6/2014 6:59:33 PM]

8

6x + 6 + 5x - 8 = 11x - 2

Added 8/6/2014 6:56:30 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/6/2014 7:01:19 PM]

8

When A = -3, A^2 = (-3)^2 = 9

Added 8/6/2014 6:57:07 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/6/2014 7:02:18 PM]

4y - 6y + 9y = -2
{-2/11}
{-2/7}
{2/7}
{2/11} **Weegy:** y = -2/7 **User:** (x - 3) - 2(x + 6) = -5
{-10}
{-4}
{8} **Weegy:** its -10. wait ill check again **User:** (x - 3) - 2(x + 6) = -5
{-10}
{-4}
{8} **Weegy:** its -10. wait ill check again **User:** 7x + 9 = 6x - 5
x = -14
x = -4
x = 4
x = 14 **Weegy:** 4-7x+10=15-6x-8
4+10=14 and 15-8=7
so now you have...
14-7x=7-6x
- - - - - - - - - - - - - - - - - - - ?
7x+7x
14=7+x
now use opposites to get
-x= -7 which equals
x=7 is your answer. **User:** 17x - 6 + 3x - 5 = x + 11 + 4x
20x - 11 = 5x + 11
20x + 1 = 5x + 11
9x = 16x **Weegy:** 20x-11=5x+11 **User:** An equation _____ has one solution.
always
sometimes
never **Weegy:** It's either a trick question, [ or the person who wrote the question is guilty of fuzzy thinking.
a linear (1st order) equation will have one solution
a quadratic (2nd order) equation will have two solutions
a cubic (3rd order) equation will have three solutions
...
an nth order equation will have n solutions.
An equation may have more than one solution, or the solution(s) may be complex, rather than real, but it will always have one solution - and sometimes more than one.
Had the question been "An equation _____ has only one solution", the answer would have been #2, "sometimes". ] **User:** An equation _____ has one solution.
always
sometimes
never **Weegy:** It's either a trick question, [ or the person who wrote the question is guilty of fuzzy thinking.
a linear (1st order) equation will have one solution
a quadratic (2nd order) equation will have two solutions
a cubic (3rd order) equation will have three solutions
...
an nth order equation will have n solutions.
An equation may have more than one solution, or the solution(s) may be complex, rather than real, but it will always have one solution - and sometimes more than one.
Had the question been "An equation _____ has only one solution", the answer would have been #2, "sometimes". ] **User:** Which of the following equations has the given solution set?
Solution set: Ø
-2m + 5 = ... (More)

Question

Expert Answered

Updated 3/12/2014 3:28:22 AM

3 Answers/Comments

7x + 9 = 6x - 5

7x - 6x = -5 - 9

x = -14

7x - 6x = -5 - 9

x = -14

Added 3/12/2014 3:26:55 AM

This answer has been confirmed as correct and helpful.

9(x - 2) = 18

9x - 18 = 18

9x = 18 + 18

9x = 36

x = 36/9

x = 4

9x - 18 = 18

9x = 18 + 18

9x = 36

x = 36/9

x = 4

Added 3/12/2014 3:28:22 AM

This answer has been confirmed as correct and helpful.

The area where one plate sinks into the asthenosphere underneath another plate is known as a subduction zonea transform boundaryan earthquake boundarya convection zone **Weegy:** The area where one plate sinks into the asthenosphere underneath another plate is known as : a subduction zone. (More)

Question

Updated 1/31/2016 11:45:20 AM

0 Answers/Comments

Simplify 8(3 - 2x).
24x - 16
16x - 24
24 - 16x User: Simplify 8(3 - 2x).
24x - 16
16x - 24
24 - 16x User: Simplify 11(2x + 3).
11x + 5
22x + 3
22x + 33 User: Simplify 3x + (-12x) - 5x.
-14x
-9x
10x
20x User: Simplify 2x + x.
2x²
3x
3x ²

Question

Updated 6/4/2014 12:43:31 AM

5 Answers/Comments

8(3 - 2x) = 24 - 16x

Added 6/4/2014 12:38:13 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/4/2014 1:27:03 PM]

11(2x + 3) = 22x + 33

Added 6/4/2014 12:41:30 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/4/2014 1:27:14 PM]

3x + (-12x) - 5x = 3x - 12x - 5x = -9x - 5x = -14x

Added 6/4/2014 12:42:09 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/4/2014 1:28:03 PM]

2x + x = 3x

Added 6/4/2014 12:42:31 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/4/2014 1:28:05 PM]

-2[9 - (x + 7)]

= -2(9 - x - 7)

= -2(2 - x)

= -4 + 2x

= -2(9 - x - 7)

= -2(2 - x)

= -4 + 2x

Added 6/4/2014 12:43:31 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/4/2014 1:29:13 PM]

One side of a square is 3x + 2. Which expression represents the perimeter?
2(3x + 2)
(3x + 2)²
4(3x + 2) **Weegy:** 9x^4. If you are satisfied with my answer, please click 'Good' on the ratings. Thank you! **User:** If x represents the number, then which of the following equations could be used to solve the problem?
4x + 6 = 94
4(x + 6) = 94
x + 6 = 4(94) **User:** Dwayne's garden is triangle-shaped with two equal sides and a third side that is 4 ft more than the length of an equal side. If the perimeter is 49 ft, how long is each side?
Which equation represents this?
2x = 49
2x + 4 = 49
3x = 49
3x + 4 = 49 **Weegy:** D)3x + 4 = 49
**User:** Thomas has $6.35 in dimes and quarters. The number of dimes is three more than three times the number of quarters. How many quarters does he have?
If q represents the number of quarters, then which of the following expressions represents the value of the number of dimes in cents?
3q + 3
6.35 - q
10(3q + 3) **Weegy:** a)3q + 3 **User:** After John worked at a job for 10 years, his salary doubled. If he started at $x, his salary after 10 years is _____.
$x
$x+ 2
$x- 2
$2x **Weegy:** If his salary doubled after 10 years it is D. $2x **User:** A man walks 10 miles in x hours. How far does he walk in one hour?
Which expression represents this?
10 + x miles
10x miles
10/x miles **User:** Which of the following could represent consecutive even integers?
x + 1, x + 2
x + 1, x + 3
2x, 2x + 1 **Weegy:** 3x - 4y = 30 **User:** The sum of three numbers is 69. If the second number is equal to the first diminished by 8, and the third number is 5 times the first. What are the numbers?
If x represents the first number, then which of the following equations could be used to solve the problem?
x = 6x - 8
69 = 6x - 8
69 = 7x - 8 **User:** The sum of two numbers is x. If one of the numbers is 12, what is the other?
12 -x
x- 12
12 +x
12x **User:** Twice a certain number is tripled. The resulting number is _____.
2x+ 3
2x- 3
(2x)3
(2x) **Weegy:** If twice a certain number is tripled, the resulting number is C. (2x)3 **User:** The value in cents ... (More)

Question

Updated 6/26/2014 9:58:18 PM

7 Answers/Comments

4 + (27 - 12·2) ÷ 2

= 4 + (27 - 24) ÷ 2

= 4 + 3/2

= 4 + 1.5

= 5.5

= 4 + (27 - 24) ÷ 2

= 4 + 3/2

= 4 + 1.5

= 5.5

Added 6/26/2014 9:55:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 9:58:44 PM]

The coefficient for 3 · 2x is 6.

Added 6/26/2014 9:56:06 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 9:58:57 PM]

In the expression (x^2 + 3), the base is x.

Added 6/26/2014 9:56:59 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 9:59:05 PM]

42 + 6 ÷ 2

= 42 + 3

= 45

= 42 + 3

= 45

Added 6/26/2014 9:57:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 10:02:36 PM]

Scientists have standardized a concise definition of life.
True
False User: Scientists distinguish whether an entity is living or nonliving by describing the _____ of life.
characteristics
value
length
quality **Weegy:** characteristics. Scientists distinguish whether an entity is living or nonliving by describing the "characteristics" of life. **User:** It is often easier to determine if an object or organism possesses the characteristics of life rather than life itself.
True
False **User:** Select all that apply.
Characteristics that are always present in living organisms are _____.
complexity
homeostasis
metabolism
heredity
movement
cells
sensitivity
reproduction (More)

Question

Updated 1/26/2016 12:00:59 PM

3 Answers/Comments

Scientists have standardized a concise definition of life. FALSE.

Added 1/26/2016 12:00:44 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/26/2016 12:14:24 PM]

It is often easier to determine if an object or organism possesses the characteristics of life rather than life itself. TRUE.

Added 1/26/2016 12:00:54 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/26/2016 12:14:35 PM]

32,562,331

questions answered

There are no comments.